2020
DOI: 10.1542/peds.2019-1275
|View full text |Cite
|
Sign up to set email alerts
|

Well-Child Care Adherence After Intrauterine Opioid Exposure

Abstract: BACKGROUND AND OBJECTIVES: For children with intrauterine opioid exposure (IOE), well-child care (WCC) provides an important opportunity to address medical, developmental, and psychosocial needs. We evaluated WCC adherence for this population. METHODS:In this retrospective cohort study, we used PEDSnet data from a pediatric primary care network spanning 3 states from 2011 to 2016. IOE was ascertained by using physician diagnosis codes. WCC adherence in the first year was defined as a postnatal or 1-month visit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 59 publications
1
24
1
Order By: Relevance
“…Our results indicate that the majority of outpatient encounters for children with a history of NAS are secondary to developmental evaluations and routine well-child checks as these were the most frequent, associated diagnostic codes in the first 3 years. In contrast to recent literature noting decreased compliance with routine well-child visits in the first 2 years, 27 we found increased diagnostic and procedural codes for preventative visits in children with NAS compared with children without. We also found greater frequencies of diagnostic and procedural codes for vaccinations in children with a history of NAS.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results indicate that the majority of outpatient encounters for children with a history of NAS are secondary to developmental evaluations and routine well-child checks as these were the most frequent, associated diagnostic codes in the first 3 years. In contrast to recent literature noting decreased compliance with routine well-child visits in the first 2 years, 27 we found increased diagnostic and procedural codes for preventative visits in children with NAS compared with children without. We also found greater frequencies of diagnostic and procedural codes for vaccinations in children with a history of NAS.…”
Section: Discussioncontrasting
confidence: 99%
“…23 Single-state studies showed higher readmission rates in children with NAS in first 30 days to 5 years, [24][25][26] and a multistate study demonstrated decreased adherence to recommended well-child checks. 27 Our recent study using a national, private insurance database showed increased utilization of all branches of the health care system including inpatient, outpatient, emergency department (ED), and prescription drugs by children with a history of NAS through 8 years. 28 Although these results aid in our understanding of longer-term health outcomes for children with NAS, they fail to explore patterns of health care use in children with public health insurance coverage, the primary insurance of infants with an NAS diagnosis.…”
mentioning
confidence: 99%
“…4 Current research suggests increased risk for morbidity, emergency department utilization, and rehospitalization after discharge in this population as well as difficulty in accessing and engaging with pediatric preventative care. 45,46 A clear plan should be established upon discharge to ensure optimal newborn care and follow-up. A complete record of the newborn's hospital stay, including maternal toxicology screenings and summary of any social work documentation, should be communicated to the primary care provider upon discharge.…”
Section: Discharge Planningmentioning
confidence: 99%
“…Regardless of whether or not NAS is treated pharmacologically, newborns with opioid exposure may experience residual symptoms of withdrawal that persist for months 4 . Current research suggests increased risk for morbidity, emergency department utilization, and rehospitalization after discharge in this population as well as difficulty in accessing and engaging with pediatric preventative care 45, 46 …”
Section: Discharge Planningmentioning
confidence: 99%
“…First, there are gaps in recommended WCC utilization. A recent cohort analysis of over 11,000 children within a multisite primary care network has shown that compared with the general population, children with intrauterine opioid exposure are 50% less likely to receive adequate WCC through the first 2 years of life (Goyal, Rohde, Chung, Short, & Patrick, 2020). Second, mothers in treatment for OUD report limited family‐centred care for their children during WCC visits.…”
Section: Introductionmentioning
confidence: 99%